Improving the Quality of Education through the Use of Interactive Methods in the Educational Process - Abduvaliyevich, Daminov Jakbarali (PT. Antis International Publisher, 2024)
This article presents the possibilities of using the entangled logical chain method to determine the level of education of students when teaching the subject